Evaluation of Patient Waiting Time at UOBK RSUD SLG Kediri - Sutrisno, Sutrisno; Wardani, Ratna; Khotib, Ahmad; Gabriel Renata Handoyo (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Waiting time is one of the components that has the potential to cause dissatisfaction. In residency the author has written various strengths, weaknesses, opportunities and threats from evaluating patient waiting times at UOBK RSUD SLG Kediri Regency. Evaluation of the waiting time at the clinic of internal medicine 92.19% and 82.3% cardiac clinic is more than 60 minutes. The waiting time for concoction drug service is 70% more than 60 minutes and finished drug service is 90% more than 30 minutes. Waiting time for patient transfer from ER to the inpatien unit is 43.48% more than 6 hours. Identification of problems has been carried out, setting priorities for solving problems and identifying strategies that can be used, namely by maximizing social media for online registration, streamlining communication between units, especially from the poly with pharmacy and making SOPs regarding consultations with DPJP. It is expected that the waiting time of outpatients, especially the cardiac polyclinic and internal medicine polyclinic, is routinely monitored every month so that it can meet the national quality indicators, namely less than 60 minutes for at least 80% of patients and the waiting time for drugs according to standards and the waiting time for transfers patients from the emergency room to hospitalization less than 6 hours, in order to increase patient satisfaction